Pengaruh Moderasi Citra Merek Terhadap Kepuasan Pelanggan Dan Loyalitas Pelanggan Pada Restoran Cepat Saji - Ferryal Abadi; Gita Nurpratiwi (Jurnal Riset Manajemen dan Bisnis, 2021)
The purpose of this study is to determine whether food quality, price, environmental location and service quality affect customer satisfaction, and whether customer satisfaction affects customer loyalty as well, and to determine whether brand image strengthens or weakens customer satisfaction and customer loyalty. This study uses a survey method with an questionnaire for data collection. This research method uses multiple linear analysis test, the population and sample of this research are customers who are located around Tangerang. The total number of samples in this study were 150 respondents. The results of this study explain that food quality has a positive and significant effect on customer satisfaction, and price has a significant positive effect on customer satisfaction, and location and environment have a positive and significant effect on customer satisfaction, and service quality has a positive and significant effect on customer satisfaction, and customer satisfaction has a positive and significant effect on customer loyalty, and brand image moderates customer satisfaction and customer loyalty.